Investigating the Sound Change in the New Zealand English Nurse Vowel /ᴈ:. Issue 4 (2nd October 2017) - Maclagan, Margaret; Watson, Catherine I.; Harlow, Ray; King, Jeanette; Keegan, Peter
Abstract : Although there have been many studies of New Zealand English (NZE) vowels, little has been written about thenurse vowel /ɜ:/. This study uses data from three groups of Māori speakers of NZE born between 1871 and 1992 to analyse changes to thenurse vowel over time. Although all these speakers are bilingual in English and Māori, we show that they are representative of NZE speakers generally. Analyses are carried out on formant frequency, vowel length, lip-rounding and vocal tract shape. The vowel space position measure (VSM) is used to analyse first and second formant movements together. Thenurse vowel in NZE has risen so that it is now close and front in the vowel space, and apparently in danger of being confused with thegoose vowel. We conclude by considering the factors that apparently keep the vowels apart and the potential effects of such a merger.